Not all phi-features are created equal: A reply to Hartmann & Heycock 2018 - BÉJAR, SUSANA; KAHNEMUYIPOUR, ARSALAN (Journal of linguistics, 2018)
Susana Béjar and Arsalan Kahnemuyipour respond to Jutta M. Hartmann and Caroline Heycock's commentary (same journal issue) on their original article "Non-canonical agreement in copular sentences" (Journal of Linguistics, 53.3, 463–499).